Anode active material layer and solid-state battery
A negative electrode active material layer with porous silicon, graphite, and inorganic electrolyte particles addresses the issue of structural destruction from high-pressure pressing, maintaining performance and capacity retention in solid-state batteries.
Patent Information
- Application Number
- JP2022152734
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-09-26
AI Technical Summary
The use of porous silicon particles as a negative electrode active material in solid-state batteries is hindered by the need for high-pressure pressing, which can destroy their porous structure and impair performance due to the deformation of sulfide solid electrolyte particles.
A negative electrode active material layer comprising porous silicon particles, graphite particles, and inorganic solid electrolyte particles, with a specific mass ratio and aspect ratio of graphite particles, is used to prevent structural destruction during pressing, maintaining the porous structure and performance.
The solution effectively suppresses volume changes in silicon particles during charging and discharging, ensuring the maintenance of the porous structure and enhancing the capacity retention rate of the solid-state battery.
Smart Images

Figure 0007609147000002 
Figure 0007609147000003 
Figure 0007609147000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode active material layer and a solid-state battery having a negative electrode active material layer. [Background technology]
[0002] A solid-state battery is a battery having a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has the advantage of being easy to simplify safety devices. Among solid-state batteries, solid-state lithium-ion batteries have attracted attention because they can provide high energy density by utilizing a battery reaction involving the movement of lithium ions.
[0003] Active materials containing silicon (Si) (silicon-containing active materials) are known as negative electrode active materials used in the negative electrode layer of batteries. Silicon-containing active materials have the advantage of having a large theoretical capacity per volume, but on the other hand, they have a problem in that their volume changes significantly during charging and discharging, which makes their characteristics prone to deterioration when they are used repeatedly.
[0004] To address such problems, it is known to use porous silicon particles to suppress the effects of volumetric changes in silicon due to charging and discharging, as disclosed in Patent Document 1. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-097017 Summary of the Invention [Problem to be solved by the invention]
[0006] By using porous silicon particles as in Patent Document 1, the effect of volumetric changes in silicon caused by charging and discharging can be suppressed.
[0007] However, the present inventors have found that: In forming the negative electrode active material layer of the solid-state battery, it is necessary to press the negative electrode active material layer with a large pressure in order to improve the contact between the particles, and in particular, when sulfide solid electrolyte particles are used, it is necessary to press the negative electrode active material layer with a large pressure in order to deform the sulfide solid electrolyte particles by pressing and improve the contact between the particles; and Pressing at such a high pressure may at least partially destroy the porous structure of the porous silicon particles, thereby preventing the porous silicon particles from exhibiting their inherent performance. [Means for solving the problem]
[0008] The present inventors have conducted extensive research and found that the above problems can be solved by the following means, and have completed the present invention. That is, the present invention is as follows.
[0009] <Aspect 1> Contains porous silicon particles, graphite particles, and inorganic solid electrolyte particles, and a ratio of the mass of the graphite particles to the total mass of the porous silicon particles and the graphite particles is 10% by mass to 25% by mass; Negative electrode active material layer. Aspect 2: The negative electrode active material layer according to aspect 1, wherein the porous silicon particles are porous clathrate silicon particles. <Aspect 3> The inorganic solid electrolyte particles are sulfide solid electrolyte particles, a ratio of a total mass of the porous silicon particles and the graphite particles to a total mass of the porous silicon particles, the graphite particles, and the inorganic solid electrolyte particles is 30% by mass to 85% by mass; and The graphite particles have an average aspect ratio of 1.5 or more; and The D50 diameter of the graphite particles is 2 to 20 times the D50 diameter of the porous silicon particles. 3. The negative electrode active material layer according to aspect 1 or 2. A solid-state battery having the anode active material layer according to any one of Aspects 1 to 3, a solid electrolyte layer, and a cathode active material layer in this order. <Aspect 5> A method for producing the negative electrode active material layer according to any one of aspects 1 to 3, comprising roll pressing. Effect of the Invention
[0010] According to the negative electrode active material layer of the present disclosure, the effect of the porous silicon particles, that is, the effect of suppressing the influence of volumetric changes in silicon due to charging and discharging, can be effectively provided in a solid-state battery. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a solid-state battery. [Diagram 2] FIG. 2 is a diagram showing the relationship between the ratio of the mass of graphite particles to the total mass of porous silicon particles and graphite particles and the porosity for the solid state batteries of Examples and Comparative Examples. [Diagram 3] FIG. 3 is a diagram showing the relationship between the ratio of the mass of graphite particles to the total mass of porous silicon particles and graphite particles and the capacity retention rate for the solid state batteries of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. However, the embodiments shown in the drawings are merely examples of the present disclosure and are not intended to limit the present disclosure.
[0013] 《Negative electrode active material layer》 The negative electrode active material layer of the present disclosure contains porous silicon particles, graphite particles, and inorganic solid electrolyte particles, and the proportion of the mass of the graphite particles to the total mass of the porous silicon particles and the graphite particles is 10 mass % to 25 mass %.
[0014] According to the negative electrode active material layer of the present disclosure, even when using porous silicon particles and inorganic solid electrolyte particles, the inherent performance of the porous silicon particles can be exhibited.Without being limited by theory, this is believed to be due to the fact that the graphite particles, i.e., the relatively hard particles having a relatively large aspect ratio, are contained in an appropriate proportion, so that the graphite particles function as a pillar structure, thereby suppressing the application of excessive pressure to the porous silicon particles during pressing and / or restraint, which is essential when using inorganic solid electrolyte particles, i.e., suppressing the destruction of the porous structure of the porous silicon particles.
[0015] The thickness of the negative electrode active material layer may be 1 μm or more, 10 μm or more, 30 μm or more, or 50 μm or more, and may be 100 μm or less.
[0016] The negative electrode active material layer of the present disclosure can be manufactured by any method, for example, by applying a negative electrode mixture slurry containing porous silicon particles, graphite particles, and inorganic solid electrolyte particles onto a substrate, drying and pressing. Here, as the press in this case, it is preferable to use a roll press in order to provide a large pressing pressure to the negative electrode active material layer. Here, the pressure of this roll press may be 10 kN / cm or more, 50 kN / cm or more, 80 kN / cm or more, or 100 kN / cm or more, and may be 500 kN / cm or less, 300 kN / cm or less, 200 kN / cm or less, or 100 kN / cm or less.
[0017] (Porous silicon particles) In the present disclosure, porous silicon particles are used as negative electrode active material particles. The porous silicon particles are silicon particles having pores inside the primary particles, and the pores can suppress the expansion and contraction of the negative electrode active material particles during charging and discharging.
[0018] In this regard, for example, the porous silicon particles may have an amount of pores having a pore diameter of 100 nm or less of 0.01 cc / g or more, 0.05 cc / g or more, or 0.10 cc / g or more, and may have an amount of pores having a pore diameter of 100 nm or less of 0.50 cc / g or less, 0.40 cc / g or less, 0.30 cc / g or less, 0.20 cc / g or less, 0.15 cc / g or less, or 0.10 cc / g or less. The amount of pores having a pore diameter of 100 nm or less is the cumulative pore volume of pores having a pore diameter of 100 nm or less. The cumulative pore volume can be determined, for example, by mercury porosimeter measurement.
[0019] The porous silicon particles can be produced by any method. Specifically, the porous silicon particles can be produced by a known method. For example, the porous silicon particles can be produced by forming particles of an alloy of silicon and another metal such as magnesium or lithium, and dissolving and removing the other metal from the alloy particles.
[0020] The size of the porous silicon particles is not particularly limited. The median diameter (D50 particle diameter) of the porous silicon particles may be, for example, 0.1 μm or more, 0.3 μm or more, or 0.5 μm or more, and may be 50.0 μm or less, 30.0 μm or less, 10.0 μm or less, 5.0 μm or less, 3.0 μm or less, or 1.0 μm or less. The median diameter of the porous silicon particles is the particle diameter (D50 diameter) at an integrated value of 50% in the volume-based particle size distribution obtained by a laser diffraction / scattering method.
[0021] The porous silicon particles may have a clathrate structure. It is preferable that the porous silicon particles have a clathrate structure, since the expansion and contraction of the porous silicon particles accompanying the charging and discharging of the battery is further reduced. Whether the porous silicon particles have a clathrate structure or not can be easily determined from Raman spectrum, XRD, or the like. The porous silicon particles may have an oxide film or may contain impurities such as carbon.
[0022] (graphite particles) In the present disclosure, graphite particles are used as negative electrode active material particles. The graphite particles are a layered compound composed of multiple graphene layers, and metal ions such as lithium ions can be inserted and removed between the graphene layers.
[0023] The size of the graphite particles is not particularly limited. The median diameter (D50 particle diameter) of the graphite particles may be, for example, 1.0 μm or more, 3.0 μm or more, or 5.0 μm or more, and may be 50 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The median diameter of the graphite particles is the particle diameter (D50 diameter) at an integrated value of 50% in a volume-based particle size distribution determined by a laser diffraction / scattering method.
[0024] The median diameter of the graphite particles may be larger than the median diameter of the porous silicon particles, for example the median diameter of the graphite particles may be at least 2 times, at least 3 times, at least 4 times, or at least 5 times the median diameter of the porous silicon particles, and may be at most 20 times, at most 10 times, at most 15 times, or at most 10 times.
[0025] Graphite particles usually have a relatively large aspect ratio. Here, the aspect ratio of graphite particles is the ratio of the long axis length to the short axis length (long axis length / short axis length). The long axis length and the short axis length can be measured by image analysis using, for example, a microscope, a scanning electron microscope (SEM), or the like. The average aspect ratio of graphite particles is the number average value of the aspect ratio measured by image analysis for graphite particles whose long axis length is equal to or greater than the median diameter, and may be 1.5 or more, 2.0 or more, or 2.5 or more, and may be 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, 4.0 or less, or 3.5 or less.
[0026] The proportion of the mass of the graphite particles relative to the total mass of the porous silicon particles and the graphite particles may be 10 mass% or more, 11 mass% or more, 12 mass% or more, 13 mass% or more, 14 mass% or more, or 15 mass% or more, and may be 25 mass% or less, 24 mass% or less, 23 mass% or less, 22 mass% or less, 21 mass% or less, or 20 mass% or less.
[0027] (Inorganic solid electrolyte particles) Any inorganic solid electrolyte particles can be used.
[0028] Examples of inorganic solid electrolyte particles include lithium lanthanum zirconate, LiPON, and Li 1+X Al X Ge 2-X Examples of the oxide solid electrolyte particles include (PO4)3, Li-SiO-based glass, and Li-Al-SO-based glass; and sulfide solid electrolyte particles such as Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5-GeS2. In particular, sulfide solid electrolyte particles, particularly sulfide solid electrolyte particles containing at least Li, S, and P as constituent elements, are preferred because of their high performance. The inorganic solid electrolyte particles may be amorphous or crystalline. Only one type of inorganic solid electrolyte particle may be used alone, or two or more types may be used in combination.
[0029] In the negative electrode active material layer, the ratio of the total mass of the porous silicon particles and graphite particles to the total mass of the porous silicon particles, graphite particles, and inorganic solid electrolyte particles (i.e., the ratio of the mass of the negative electrode active material to the total mass of the negative electrode active material and inorganic solid electrolyte particles) may be 30 mass% or more, 40 mass% or more, or 50 mass% or more, and may be 85 mass% or less, 80 mass% or less, 75 mass% or less, 70 mass% or less, 65 mass% or less, or 60 mass% or less.
[0030] The thickness of the negative electrode active material layer may be 1 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 30 μm or more, or 50 μm or more, and may be 100 μm or less, 80 μm or less, 60 μm or less, 40 μm or less, or 30 μm or less.
[0031] (others) The negative electrode active material layer may contain, in addition to the porous silicon particles, graphite particles, and inorganic solid electrolyte particles, an electrolyte solution, a conductive assistant, and / or an organic binder.
[0032] The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be, for example, a non-aqueous electrolyte. For example, the electrolyte may be a carbonate-based solvent in which a lithium salt is dissolved at a predetermined concentration. Examples of the carbonate-based solvent include fluoroethylene carbonate (FEC), ethylene carbonate (EC), and dimethyl carbonate (DMC). Examples of the lithium salt include hexafluorophosphate. However, it may be preferable that the negative electrode active material layer does not contain an electrolyte in order to provide performance due to inorganic solid electrolyte particles.
[0033] Examples of the conductive assistant include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.
[0034] Examples of the organic binder include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, polyacrylic acid-based binders, etc. Only one type of organic binder may be used alone, or two or more types may be used in combination.
[0035] 《Solid-state battery》 The solid-state battery of the present disclosure includes, in this order, the anode active material layer, the solid electrolyte layer, and the cathode active material layer of the present disclosure. In particular, the solid-state battery of the present disclosure includes, in this order, the anode current collector layer, the anode active material layer of the present disclosure, the solid electrolyte layer, the cathode active material layer, and the cathode current collector layer.
[0036] In the present disclosure, examples of the solid-state battery include a solid-state lithium ion battery, a solid-state sodium ion battery, a solid-state magnesium ion battery, and a solid-state calcium ion battery. Among these, a solid-state lithium ion battery and a solid-state sodium ion battery are preferred, and a solid-state lithium ion battery is particularly preferred. In addition, the solid-state battery of the present disclosure is preferably a solid-state battery that uses sulfide solid electrolyte particles as solid electrolyte particles, i.e., a sulfide solid battery.
[0037] The sulfide solid state battery of the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery. This is because secondary batteries can be repeatedly charged and discharged and are useful, for example, as in-vehicle batteries. Therefore, the sulfide solid state battery of the present disclosure is preferably a solid lithium ion secondary battery.
[0038] In the present disclosure, the battery stack may be a monopolar type battery stack or a bipolar type battery stack.
[0039] The battery stack of the solid-state battery of the present disclosure may be constrained in the stacking direction during use, which can improve ionic and electronic conductivity within and between each layer of the battery stack during charging and discharging, and further promote the battery reaction.
[0040] In this case, the restraining force is not particularly limited and may be, for example, 1.0 MPa or more, 1.5 MPa or more, 2.0 MPa or more, or 2.5 MPa or more. The upper limit of the restraining force is not particularly limited and may be, for example, 50 MPa or less, 30 MPa or less, 10 MPa or less, or 5 MPa or less.
[0041] (Positive electrode current collector layer) The positive electrode collector layer used in the solid-state battery of the present disclosure can be any of those commonly used as a positive electrode collector layer for secondary batteries. The positive electrode collector layer may be in the form of a foil, a plate, a mesh, a punched metal, a porous, or a foam. The positive electrode collector layer may be a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector layer may be made of a plurality of metal foils. Examples of metals constituting the positive electrode collector layer include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel.
[0042] (Cathode active material layer) The positive electrode active material layer used in the solid-state battery of the present disclosure includes a positive electrode active material, and may further include an electrolyte, a conductive assistant, a binder, etc. In addition, the positive electrode active material layer may also include various other additives. The contents of the positive electrode active material, electrolyte, conductive assistant, binder, etc. in the positive electrode active material layer may be appropriately determined according to the desired battery performance.
[0043] The electrolyte that can be contained in the positive electrode active material layer may be a solid electrolyte, a liquid electrolyte (electrolytic solution), or a combination thereof.
[0044] In the positive electrode active material layer, the proportion of the mass of the positive electrode active material particles relative to the total mass of the positive electrode active material particles and the inorganic solid electrolyte particles may be 30 mass% or more, 40 mass% or more, 50 mass% or more, 60 mass% or more, 70 mass% or more, or 80 mass% or more, and may be 95 mass% or less, 90 mass% or less, 85 mass% or less, or 80 mass% or less.
[0045] The thickness of the positive electrode active material layer may be 1 μm or more, 10 μm or more, 30 μm or more, or 50 μm or more, and may be 100 μm or less, 80 μm or less, 60 μm or less, or 40 μm or less.
[0046] <Electrolyte layer> The electrolyte layer used in the solid-state battery of the present disclosure includes at least an electrolyte. The electrolyte layer may include a solid electrolyte, and may further include a binder or the like. In this case, the content of the solid electrolyte and the binder or the like in the electrolyte layer is not particularly limited. The electrolyte layer may also include various additives. The electrolyte layer may also include a liquid component together with the solid electrolyte. Alternatively, the electrolyte layer may include an electrolytic solution, and may further include a separator or the like for holding the electrolytic solution and preventing contact between the positive electrode and the negative electrode.
[0047] (Negative electrode current collector layer) The negative electrode layer used in the solid-state battery of the present disclosure may include a negative electrode current collector layer in contact with the negative electrode active material layer. Any of the negative electrode current collector layers commonly used for battery negative electrode current collector layers can be used. The negative electrode current collector layer may be in the form of a foil, a plate, a mesh, a punched metal, a porous, or a foam. The negative electrode current collector layer may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, metal foil is excellent in terms of ease of handling. The negative electrode current collector layer may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode current collector layer include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector layer may contain at least one metal selected from Cu, Ni, and stainless steel. EXAMPLES
[0048] Example 1 <Preparation of Positive Electrode Layer> A polypropylene container was charged with butyl butyrate as a dispersion medium, a 5 mass% butyl butyrate solution of a polyvinylidene fluoride binder, LiNi1 / 3Co1 / 3Mn1 / 3O2 with an average particle size of 6 μm as positive electrode active material particles, Li2S-P2S5-based glass ceramic as sulfide solid electrolyte particles, and vapor-grown carbon fiber as a conductive additive, to obtain a positive electrode mixture slurry.
[0049] Here, in the positive electrode active material layer, the mass ratio of the positive electrode active material particles to the solid electrolyte particles was 85: 15. The positive electrode active material layer had a thickness of 35 μm.
[0050] This positive electrode mixture slurry was stirred for 30 seconds with an ultrasonic dispersing device (UH-50, manufactured by SMT), shaken for 3 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.), and stirred for 30 seconds with the ultrasonic dispersing device. After that, the positive electrode mixture slurry was applied to an aluminum foil (manufactured by Showa Denko) as a positive electrode current collector layer by a blade method using an applicator, and dried for 30 minutes on a hot plate at 100°C to obtain a positive electrode layer having a positive electrode active material layer and a positive electrode current collector layer.
[0051] <Preparation of negative electrode layer> Butyl butyrate as a dispersion medium, a 5 wt% butyl butyrate solution of a PVDF-based binder, a conductive assistant (vapor-grown carbon fiber), porous silicon and graphite particles as negative electrode active materials, and sulfide solid electrolyte particles (Li2S-P2S5-based glass ceramic) were added to a polypropylene container to obtain a negative electrode mixture slurry.
[0052] Here, in the negative electrode active material layer, the mass ratio of the negative electrode active material particles to the solid electrolyte particles was 55:45. The mass ratio of the graphite particles to the total mass of the porous silicon particles and the graphite particles was 10 mass%. The thickness of the negative electrode active material layer was 21 μm. The porous silicon particles had a median diameter (D50) of about 1.0 μm. The graphite particles had a median diameter (D50) of about 10 μm and an aspect ratio of about 3.
[0053] This negative electrode mixture slurry was stirred for 30 seconds with an ultrasonic dispersing device (UH-50, manufactured by SMT) and then shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.) After that, the negative electrode mixture slurry was applied to a copper foil (manufactured by UACJ) as a negative electrode current collector layer by a blade method using an applicator, and dried for 30 minutes on a hot plate at 100°C to obtain a negative electrode layer having a negative electrode active material layer and a negative electrode current collector layer.
[0054] (Preparation of solid electrolyte layer with release sheet) A polypropylene container was charged with heptane, a 5 wt % heptane solution of a butyl rubber binder, and a sulfide solid electrolyte (Li2S-P2S5 glass ceramic) to obtain a solid electrolyte mixture slurry.
[0055] This solid electrolyte mixture slurry was stirred for 30 seconds with an ultrasonic dispersing device (UH-50, manufactured by SMT), and the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.) After that, the solid electrolyte mixture slurry was applied onto an aluminum foil as a release layer by a blade method using an applicator, and dried for 30 minutes on a hot plate at 100°C to obtain a solid electrolyte layer with a release sheet.
[0056] <Battery Construction> The solid electrolyte layer with the release sheet and the positive electrode layer obtained as described above were laminated in the order of release sheet, solid electrolyte layer, positive electrode active material layer, and positive electrode current collector layer. This laminate was roll-pressed at a pressure of 100 kN / cm and a press temperature of 165° C., and the release sheet was peeled off to obtain a positive electrode laminate.
[0057] The solid electrolyte layer and the negative electrode layer with the release sheet obtained as described above were laminated in the order of release sheet, solid electrolyte layer, negative electrode active material layer, and negative electrode current collector layer. This laminate was roll-pressed at a pressure of 60 kN / cm and a press temperature of 25° C., and the release sheet was peeled off to obtain a negative electrode laminate.
[0058] The solid electrolyte layer with the release sheet and the negative electrode laminate obtained as described above were laminated in the order of release sheet, solid electrolyte layer (intermediate solid electrolyte layer), solid electrolyte layer, negative electrode active material layer, and negative electrode current collector layer. This laminate was flat uniaxially pressed for 10 seconds at a pressure of 100 MPa and a press temperature of 25° C., and the release sheet was peeled off to obtain a negative electrode laminate with an intermediate solid electrolyte layer.
[0059] The negative electrode laminate with an intermediate solid electrolyte layer and the positive electrode laminate were produced so that the area of the negative electrode laminate with an intermediate solid electrolyte layer was larger than the area of the positive electrode laminate.
[0060] The positive electrode laminate and the negative electrode laminate with the intermediate solid electrolyte layer obtained as described above were laminated in the order of the positive electrode current collector layer, the positive electrode active material layer, the solid electrolyte layer, the intermediate solid electrolyte layer, the solid electrolyte layer, the negative electrode active material layer, and the negative electrode current collector layer. The laminate was flat uniaxially pressed at a pressure of 200 MPa and a temperature of 120° C. for 1 minute to obtain a solid battery of Example 1.
[0061] <Porosity evaluation> The porosity was determined by measuring the ratio of the void volume in the negative electrode active material layer to the total volume of the negative electrode active material layer. The porosity of the negative electrode active material layer was calculated using the following formula: Porosity (%)=(1-x / y)×100 x: The total volume of each material obtained by dividing the weight of each material constituting the negative electrode active material layer by the true density of each material y: Apparent volume obtained from the actual dimensions of the negative electrode active material layer
[0062] <Evaluation of Capacity Retention Rate> The solid-state battery obtained as described above was restrained at a predetermined restraining pressure (5 MPa) using a restraining jig, discharged at 1.0 C to 3.0 V, charged at 0.33 C at a constant current-constant voltage to 4.35 V, and discharged at 0.33 C at a constant current-constant voltage to 3.00 V to determine the initial capacity. After that, a charge-discharge test at 2.0 C was repeated 200 times, and the retention rate from the initial capacity was calculated.
[0063] Examples 2 to 3 and Comparative Examples 1 to 3 In the preparation of the negative electrode layer, the mass ratio of the porous silicon and graphite as the negative electrode active material was changed as shown in Table 1, and the solid-state batteries of Examples 2 to 3 and Comparative Examples 1 to 3 were prepared and evaluated in the same manner as in Example 1.
[0064] Evaluation Results For Examples 1 to 3 and Comparative Examples 1 to 3, the ratio of the mass of the graphite particles to the total mass of the porous silicon particles and graphite particles as the negative electrode active material, the porosity of the negative electrode active material layer, and the capacity retention rate of the solid state battery are shown in Table 1 and FIGS.
[0065] [Table 1]
[0066] As shown in Table 1 and FIG. 1, in Examples 1 to 3 in which the ratio of the mass of the graphite particles to the total mass of the porous silicon particles and the graphite particles was 10 mass%, 15 mass%, and 20 mass%, respectively, the porosity of the negative electrode active material layer was relatively large, and the capacity retention rate of the solid battery was also relatively large. This is considered to be because the negative electrode active material layer contains a moderate amount of graphite particles, and the graphite particles function as pillars, thereby suppressing the collapse of the pores in the porous silicon particles. In addition, such pores in the porous silicon particles are useful for absorbing the expansion and contraction caused by the charge and discharge of the battery, thereby improving the capacity retention rate of the battery.
[0067] In contrast, in Comparative Example 1 in which graphite particles were not used, the above-mentioned pillars were not present, and therefore the voids in the porous silicon particles were crushed, which is thought to have resulted in a relatively small porosity in the negative electrode active material layer and a relatively small capacity retention rate of the solid-state battery.
[0068] In Comparative Example 1, in which the ratio of the mass of the graphite particles to the total mass of the porous silicon particles and the graphite particles was 5 mass%, the porosity of the negative electrode active material layer was relatively small and the capacity retention rate of the solid battery was also relatively small, even compared to Comparative Example 1 in which no graphite particles were used. This is believed to be because the small amount of graphite particles promoted the collapse of the porous silicon particles.
[0069] Furthermore, in Comparative Example 3, in which the ratio of the mass of the graphite particles to the total mass of the porous silicon particles and the graphite particles was 30 mass%, the porosity of the negative electrode active material layer was relatively small and the capacity retention rate of the solid-state battery was also relatively small, even compared to Comparative Example 1, in which no graphite particles were used. This is believed to be because the amount of the porous silicon particles was relatively small, and therefore the amount of voids provided by the mechanism of the porous silicon particles was reduced. [Explanation of symbols]
[0070] 11 Positive electrode current collector layer 12 Cathode active material layer 31, 32, 33 Solid electrolyte layer 21 Negative electrode current collector layer 22 Negative electrode active material layer 100 solid state battery
Claims
1. The porous silicon particles, the graphite particles, and the inorganic solid electrolyte particles are included, a ratio of the mass of the graphite particles to the total mass of the porous silicon particles and the graphite particles is 10 mass% to 25 mass%, The graphite particles have an average aspect ratio of 1.5 or more; and The D50 diameter of the graphite particles is 2 to 20 times the D50 diameter of the porous silicon particles. Negative electrode active material layer.
2. The negative electrode active material layer according to claim 1 , wherein the porous silicon particles are porous clathrate silicon particles.
3. The inorganic solid electrolyte particles are sulfide solid electrolyte particles, and a ratio of a total mass of the porous silicon particles and the graphite particles to a total mass of the porous silicon particles, the graphite particles, and the inorganic solid electrolyte particles is 30% by mass to 85% by mass; The negative electrode active material layer according to claim 1 .
4. A solid-state battery comprising the anode active material layer according to claim 1, a solid electrolyte layer, and a cathode active material layer in this order.
5. The method for producing a negative electrode active material layer according to claim 1 , further comprising roll pressing.
Citation Information
Patent Citations
Conductive paste for forming solar cell electrode and solar cell
JP2018206530A
Composite particle for negative electrode active material
JP2021097017A
Manufacturing method of all-solid battery
JP2022020211A
All-solid-state battery
JP2022094317A
All-solid battery
JP2022097800A